(untitled) (Research, Society and Development, 2025)
The 1980s were marked by the identification of the human immunodeficiency virus (HIV) as the etiological agent of Acquired Immunodeficiency Syndrome (AIDS), which had a major impact on health authorities since its discovery. In Brazil, in regions with a low HDI, there are still flaws in prenatal care that contribute to the increase in the incidence of cases, especially in children. The objective was to evaluate the correlation between the HDI and the incidence of HIV/AIDS in the Brazilian pediatric population. Open secondary data were used, online, through DataSUS and statistical analysis was performed with the Spearman test in the R software, adopting 5% significance, without the need for ethical approval. The data found demonstrate that in the years 2019-2023 the incidence of HIV in Brazilian children was higher in regions with the lowest HDI, especially in children under 5 years of age, in the North and South regions. Over the years, there was a general reduction in cases, but regional inequalities persisted. The age group from 5 to 12 years old showed a lower incidence, but also with relevant variations between regions. There was an inverse and moderate correlation between IDHM and incidence, indicating that the lower the IDHM, the higher the incidence. Based on the information obtained, it is possible to conclude in this study that there is a significant correlation between low HDI and a higher incidence of HIV/AIDS in children, varying according to the age group and year analyzed, prioritizing the importance of public primary and secondary prevention policies adapted to regional realities.